Simple and efficient synthesis of thysanone methyl ether - Bulbule, Vivek J.; Koranne, Priti S.; Deshpande, Vishnu H.; Borate, Hanumant B. (Tetrahedron, 2007)
The synthesis of thysanone methyl ether is achieved by employing semivioxanthin methyl ether, which in turn is prepared by the tandem Michael addition of an anion of orsellinate to a substituted dihydropyrone. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: human pathogen; Michael addition; orsellinate derivative; semivioxanthin

Transesterification of alpha-haloesters and beta-ketoesters over Mg-Al-hydrotalcites (HT)-like anionic clays - Bulbule, Vivek J.; Borate, Hanumant B.; Munot, Yogesh S.; Deshpande, Vishnu H.; Sawargave, Sangmeshwer P.; Gaikwad, Abaji G. (Journal of Molecular Catalysis A-Chemical, 2007)
Transesterification of alpha-haloesters was achieved by reaction of alcohols in the presence of Mg-Al-HT-like anionic clays. beta-Ketoesters were also transesterified under similar conditions on reaction with alcohols with a wide variety of functional groups. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: alpha-haloesters; beta-ketoesters; heterogeneous catalyst; Hydrotalcites; transesterification